Analisis Prospektif Desa Patutrejo Berbasis Blue Economy Development - Rahmania Mustahidda; Sugiharti Sugiharti; Maulana ihsan (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The blue economy is based on the principle of the sustainable use of marine resources directed at economic growth by utilizing marine-based resources. The objective of this research is to analyze the strategy structure and analyze priority strategies for Blue Economy Development in the Maritime Tourism sector in Patutrejo Village with environmental, tourism, economic, and social dimensions. Methodology: Data collection was carried out by determining the elements and detailing them with the help of experts based on specific expert criteria through interviews, focus group discussions, and validation. Interpretive structural modeling (ISM) and MICMAC analysis tools are used to determine elements with high driver power and low dependence values as priority strategies. Results: From the results of the analysis of priority strategies in this research, they include Environmental Elements (L): Water Conservation (L1) and Carrying Capacity (L2); Tourism Elements: Tourist Attractions (P4); Economic Elements: Tourism Industry Opportunities (E1) and Retributions (E2); Social Elements: Welfare (S2); Institutional Element: Central Government Support (K1). Conclusions: The analysis recommends a strategic approach to developing a blue economy in Patutrejo Village by focusing on environmental conservation, institutional strengthening, and local community empowerment to support sustainable marine-based tourism. Five key elements Environment, Tourism, Economy, Social, and Institutional were assessed using the ISM-MICMAC method. High-driving, low-dependence sub-elements identified include water conservation, tourism attraction development, local economic opportunities, community welfare through creative industries, and central government support for village tourism programs. Limitations: This study has limitations in that the development analysis is still general. For further research, a strategic analysis was carried out specifically in certain fields. Contribution: We hope that this can be a recommendation for determining strategies for the development and sustainability of the blue economy for managers and stakeholders in the marine tourism sector.